THE INFLUENCE OF WEAK LAYER EXISTENCE ON THE DYNAMIC SAFETY FACTOR OF THE SLOPE DUE TO BLASTING VIBRATION USING NEWMARK DISPLACEMENT ANALYSIS - Akbar, Fauzil
Slope stability is one of the essential components that must be considered in civil and mining construction. There are several factors that can cause landslides on the slopes, such as rock conditions that are naturally not too strong in maintaining slope stability or several structures such as weak layer and joint that can affect the strength of the slope. In addition, blasting vibrations are one of the external factors that can produce compressive waves that can cause slope instability. Therefore, an analysis was carried out on the effect of the presence of a weak layer structure on the dynamic stability of the slope due to blasting vibration using Newmark Displacement Analysis. To get the value of the Dynamic Safety Factor (SF) of the slope, it is necessary to reduce the resisting force on the slope by gradually reducing the cohesion value and internal friction angle using the Strength Reduction Factor. The larger the SRF, the greater the displacement that occurs. By using the critical displacement parameter of 5 mm, the Dynamic Safety Factor value is obtained for each condition to be analysed. From the results of the analysis, it can be concluded that slope stability can decrease following the conditions and orientation of the weak layer present on the slope.